Web Access Analyser for Distance Education Environment - Atan, Rodziah (1998)
Distance Education implementation has been greatly influenced by the changing of the current sophisticated technologies. Internet and World Wide Web (WWW) have enabled the rapid growth of distance education technology. The Internet is a huge database that connects most of the information source centers worldwide. This technology is equipped with the existence of WWW that ease accesses to the sources. With these technologies, distance education can be implemented properly. An approach been developed is the implementation of distance education through WWW. Learning modules are kept in a Web server while the student can access the modules from scattered terminals linked to the server via the network. It is a method of module delivery to the students that which are easier and faster. Even though distance education requires individual capability to manage the time and learning effort, the educators still have the responsibilities in evaluating their students' achievements. It is easier to evaluate on-campus students compared to distance learners. If the educators can evaluate on-campus students through their attendance and work performance, an appropriate approach to evaluate out-campus students' effort and commitment is necessary. There is a file that is specially created by a Web server which keeps and lists all access requests and transaction information made to the files kept within the server. This particular file is known as an "access_log" file. There has been a substantial effort to manipulate the file, for example, this study used "access_log" file to filter out information to produce students' distance module access statistics which is able to assist distance educators to evaluate distance students' commitment as well as to measure modules' design efficiency.